FLUORESCENCE ANALYSIS, PHYTOCHEMICAL, AND ANTIOXIDANT ACTIVITIES IN LEAVES AND STEM OF EMBELIA RIBES BURM. F - VIDYA KAMBLE; NIKHIL GAIKWAD (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study is to carry out fluorescence analysis, phytochemical, and antioxidant activities using different solvent extract in leaves and stem of Embelia ribes. Methods: In the present study, fluorescence analysis, phytochemical, and antioxidant activities of leaves and stem of E. ribes are carried out using standard procedures. Result: The fluorescence analysis under visible and ultraviolet light for leaves and stem powder of E. ribes treated with various chemical reagents shown different fluorescence effect. In the phytochemical analysis, the methanolic extract of leaves has shown the highest total alkaloid content (19.05±0.42 mg CE/g DW), followed by the stem. The methanolic extract of stem exhibited highest total phenolic content (59.82±2.98 mg GAE/g DW), and ethanolic extract showed highest total flavonoid content (10.05±0.36 mg RE/g DW), followed by leaves. The ethanolic extract of stem possesses highest antioxidant activity toward 1,1-diphenyl-2-picrylhydrazyl (DPPH) (84.86±0.11%), whereas methanolic extract of stem reported highest FRAP activity (72.22±0.31 mg Fe+2E/g DW), followed by leaves. Antioxidant activities (DPPH and FRAP) were significantly correlated with TPC. Conclusion: The results of the present study revealed that the fluorescence analysis of leaves and stem of E. ribes can be helpful for the standardization and quality control of indigenous drug. Both leaves and stem serve as the good source of secondary metabolite and antioxidant agents.